An exploratory study of eco-oriented consumer segments at a retail store. (18th August 2011) - Solberg, Birger; Veisten, Knut
This paper reports on a segmentation study of eco-oriented customers of wood products. Convenience samples of customers at IKEA retail stores in England and Norway were surveyed on purchase behaviour and their weighing of product attributes. The interviews took part beside an existing IKEA dining table of pine, and they were also presented a designed prototype eco-label that should give a guarantee of origin of the wood in sustainably managed forests. A cluster-based segmentation was performed based on individual willingness-to-pay estimates and three wood furniture attribute dimensions. The segmentation could be confirmed by dimensions of environmentalism with respect to products or attitudes. Although a non-probabilistic sampling was applied, the estimated sizes of the eco-oriented segments correspond well with similar research based on larger representative samples of the populations. The English eco-oriented IKEA customers could be re-clustered into three sub-segments with different demographic characteristics, providing operational segments for targeted marketing.